Towards a Common Academic Training in Librarianship: The Colombian Case - Vallejo Sierra, Ruth Helena (2016)
This article analyzes the librarianship academic formation, as part of the investigation Librarianship as a profession in Colombia, presenting a comparative analysis of training in Colombia with the Spanish Information and Documentation formation; indicating their common points and their differences; trying to show the main areas in which it could be agreement. In order to establish the common content that should be the obligatory core curriculum for any librarianship program in Colombia.